Two Illustrations of the Quantity Theory of Money: Breakdowns and Revivals - Sargent, Thomas J; Surico, Paolo (American Economic Review, 2011)
By extending his data, we document the instability of low-frequency regression coefficients that Lucas (1980) used to express the quantity theory of money. We impute the differences in these regression coefficients to differences in monetary policies across periods. A DSGE model estimated over a subsample like Lucas's implies values of the regression coefficients that confirm Lucas's results for his sample period. But perturbing monetary policy rule parameters away from the values estimated over Lucas's subsample alters the regression coefficients in ways that reproduce their instability over our longer sample. (JEL C51, E23, E31, E43, E51, E52)